A collaborative 14NH3 IR spectroscopic analysis at 6000 cm−1. (April 2022) - Huang (黄新川), Xinchuan; Sung, Keeyoon; Toon, Geoffrey C.; Schwenke, David W.; Lee, Timothy J.
Highlights: Laboratory measurement and theoretical analysis for 14 NH3 IR spectra in 5600–6300 cm −1 . Assigned definitive rovibrational quantum numbers to 1602 transitions pertaining to 809 upper levels and eight vibrational bands. Good for heff models. The JPL+Ames (JA) line list reports 87 new lines and 179 new assignments. Other assignments agree with Cacciani et al. for 1278 transitions. Band-by-band quality check uses the δΕ and δΔ consistency analysis. The Ames HSL-Pre3 line positions are still more accurate than C2018 for this range. The JA lists of 14 NH3 transitions and levels are reported in supplementary files. Abstract: We report new results from combined efforts of laboratory measurements and theoretical analysis for 14 NH3 in the 5600–6300 cm −1 region, based on Kitt Peak spectra previously used in the study of the 6300–7000 cm −1 region [Sung et al., JQSRT 2012, 113:1066]. Definitive rovibrational quantum numbers were assigned for 1602 transitions pertaining to 809 upper levels and eight vibrational bands: 0111 E, 0111 A, 1101, 0310, 0211, 1300, 0103 and 0302. When compared to the results from Cacciani et al. [JQSRT 2020, 258:107, 334], our results, termed as the "JPL+Ames 2021" list (or JA list), showed good agreement for the assignment of 1278 transitions. We have further made new assignments for 179 transitions that were not assigned in their work, plus assignments for 87 new lines reported for the first time. Excellent agreement (± 0.002 cm −1 ) was observed in the line positions between this work and Cacciani et al., with no systematic discrepancies. Remaining discrepancies on the assignments have been attributed to line blendings, unaccounted resonances, the uncertainties of reference line lists, and limited transition-matching accuracy. An empirical line list (JPL) and a semi-empirical line list adopting the UCL-C2018 [Coles et al., JQSRT 2018, 219:199] intensity with the Ames HSL-Pre3 based line positions were employed as the major reference for our analysis. In addition to the line position / intensity measurements and cross-validation through combination difference analysis, part of the work has also required manual matches for valid transition and level pairs and checking the consistency and patterns of δΕ Calc-Obs, inversion splittings Δa-s, etc. Band-by-band discussions are presented on the missing intensity of ν2 +3ν4 (0103), the unusual sensitivity of ν1 +3ν2 (1300) s levels, the borrowed intensity of 6ν2 (0600), and potential outliers of ν1 +ν2 +ν4 (1101), etc. These will be the topics in our future work.